2013
DOI: 10.1007/s12046-013-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous development and airworthiness certification of 15–5 PH precipitation hardenable stainless steel for aircraft applications

Abstract: In this paper, we discuss the optimization of chemical composition, processing (forging and rolling) and heat treatment parameters to obtain the best combination of mechanical properties in case of a Fe-15Cr-5Ni-4Cu precipitation hardenable stainless steel. The ε-copper precipitates that form during aging are spherical in shape and coherent with the matrix and principally provide strengthening in this alloy. The orientation relationship is found to be Kurdjumov-Sachs (K-S), which is common in fcc-bcc systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Depending on the alloy, this precipitation involves most classically Cu, such as in the 15-5 Precipitation hardening (PH) or 17-4PH alloys, NiAl such as in the 13-8PH alloy or even Ni 3 (Mo,Ti). Tailoring the characteristics of this precipitation in terms of volume fraction and size allows adjusting the balance of the steel in terms of yield strength (or ultimate tensile strength) and fracture toughness [2,3]. Thus, the Cu precipitation sequence in Fe based alloys [1,[4][5][6][7][8] and its impact on mechanical properties of PH stainless steels 17-4PH and 15-5PH [3,[9][10][11][12][13][14] has been thoroughly investigated during the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the alloy, this precipitation involves most classically Cu, such as in the 15-5 Precipitation hardening (PH) or 17-4PH alloys, NiAl such as in the 13-8PH alloy or even Ni 3 (Mo,Ti). Tailoring the characteristics of this precipitation in terms of volume fraction and size allows adjusting the balance of the steel in terms of yield strength (or ultimate tensile strength) and fracture toughness [2,3]. Thus, the Cu precipitation sequence in Fe based alloys [1,[4][5][6][7][8] and its impact on mechanical properties of PH stainless steels 17-4PH and 15-5PH [3,[9][10][11][12][13][14] has been thoroughly investigated during the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…The material presented the following tensile properties, according to ASTM E‐8M: 1029.7 MPa for yielding stress, 1079.7 MPa for ultimate tensile stress, and 9.0% of total elongation. Its microstructure consists of fine grains with lath martensite and small carbides, as typical for the H1025 hardening treatment condition (Kumar et al, ).…”
Section: Practical Description Of the Correlative Fractography Methodsmentioning
confidence: 99%
“…Paulo Davim et al [3] reported the importance of predicting surface integrity of 15-5 PH stainless steel which makes more attention in nuclear and aerospace applications. Kumar et al [4] reported that 15-5 PH is more predominant than 17-4 PH stainless steel. In the solution treated condition this material can be machined at the rate similar to SS 304.…”
Section: Introductionmentioning
confidence: 99%